Evaluation of the results of treatment of hallux valgus using the closed wedge osteotomy technique and fixation with Kirchner wires. - سعد معن (Latakia University Journal -Medical Sciences Series, 2024)
Objective : to evaluate the functional results of the treatment of hallux valgus patients using the technique of closed wedge osteotomy and fixation with Kirchner wires, to study the extent to which this technique can be applied as a more common and easy means of Appeal. Materials and methods : this study included 28 feet in 25 patients from Al-Assad and Tishreen University Hospitals in Latakia between 2006 and 2018. All patients underwent surgical treatment with closed wedge osteotomy and fixation with Kirchner wires after appropriate clinical and radiological evaluation. Removal of the splint after 4-6 weeks and rehabilitation was recommended for all patients after surgery and patients were followed up at maximum intervals 12 months of treatment. Results: the study sample consisted of 28 feet in 25 female patients and there were no males in the study, the average age of the patients was 41 years ( ranging from 20 to 62), the follow – up period extended over 12 months, and the family story was present in 80% of the patients. The clinical evaluation after surgery resulted in 72% satisfaction (18 patients) with the results while 28% (7 patients) were not satisfied, the results were excellent and good at 72% of patients (18 patients), acceptable results at 16% ( 4 patients ) and poor results at 12% (3 patients (. The complications varied between delayed union (24%), malunion 4%, relapse 4%, infection around the entrance to the wires 4%, SODIC’s syndrome 4%, metatarsophalangeal joint apoplexy 56%, but only two patients complained of symptoms. Conclusion: this study showed the positive results of the treatment of hallux valgus cases using the closed wedge osteotomy technique and fixation with Kirchner wires, the importance of this surgical technique in managing these cases, and its positive impact on rehabilitation.